2010
DOI: 10.1037/a0018603
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Posttraumatic Cognitions Inventory (PTCI) in a German sample of individuals with a history of trauma.

Abstract: This study examined the psychometric properties of the 33-item Posttraumatic Cognitions Inventory (Foa, Ehlers, Clark, Tolin & Orsillo, 1999) in 213 accident-related traumatized individuals and in 190 interpersonally traumatized individuals. Confirmatory factor analyses generally supported the original 3-factor structure "Negative Cognitions about Self" (SELF), "Negative Cognitions about World" (WORLD), and "Self-Blame" (BLAME) of the scale, after four redundant items were excluded. However, in line with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 35 publications
6
51
0
3
Order By: Relevance
“…However, the total scale and both subscales correlated higher with depression and anxiety than with PTSS. These findings are in line with previous studies of posttraumatic cognitions in adulthood [36,34] and childhood [15,16]. Additionally, after controlling for depression or anxiety, the partial correlations between dysfunctional trauma-related cognitions and PTSS remained distinctly lower.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the total scale and both subscales correlated higher with depression and anxiety than with PTSS. These findings are in line with previous studies of posttraumatic cognitions in adulthood [36,34] and childhood [15,16]. Additionally, after controlling for depression or anxiety, the partial correlations between dysfunctional trauma-related cognitions and PTSS remained distinctly lower.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that the association between the feeling of a disturbing and permanent change and an incompetent person in a scary world and the severity of PTSS can at least partly attributed to symptoms of depression and anxiety. Multiple explanations for the strong association between dysfunctional trauma-related cognitions and depression and anxiety have been proposed: 1) PTSD is often accompanied by depression and anxiety [15]; 2) dysfunctional posttraumatic cognitions are not restricted to having a role only in the maintenance of PTSD [15]; 3) pretrauma depression and anxiety might be risk factors for dysfunctional trauma-related cognitions [34]; and 4) dysfunctional trauma-related cognitions could be more a sign of depression than a distinct psychopathological construct or mechanism in their own right [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although negative posttraumatic cognitions are most strongly associated with interpersonal traumas (Lilly, ; Müller et al., ), noninterpersonal traumas can also disrupt beliefs about the self, others, and the world. For example, after an earthquake, individuals may experience self‐blame or regret about preearthquake behaviors (O'Connell, Abbott, & White, ), which could contribute to more general negative views of the self.…”
Section: Risk For Subsequent Victimizationmentioning
confidence: 99%
“…For example, self‐blame was not related to PTSD symptoms severity, in some samples of motor vehicle accident survivors (Beck et al, ; Cieslak, Benight, & Caden Lehman, ). A previous study showed that self‐blame correlated with PTSD in samples of individuals who had interpersonal trauma but not in samples with accident‐related trauma (Müller et al, ). On the contrary, another study showed that negative thoughts about the world and self‐blame showed significant associations with PTSD in the sample of motor vehicle accident survivors but not in the sample of interpersonal violence survivors (Beck, Jones, Reich, Woodward, & Cody, ).…”
Section: Introductionmentioning
confidence: 96%